PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) MENGGUNAKAN MEDIA PHYSICS CIRCUIT UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMPN 34 PEKANBARU - Dwira Yulfia; Yennita '; Zuhdi Ma’ruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to describe and find out the improvement of the learning outcomes of students by applying cooperative learning model type TGT using media physics circuit in the main optical subject. The design of this research was a pre-experimental with intact-group comparison design. This research subjects were students of VIII class at SMPN 34 Pekanbaru it consists of 80 students, divided into class is experimental and control class. Data collection instruments in this research was test cognitif of learning outcomes to be evaluation in the end of meeting with consists of 20 cognitif questions. The analysis of the data uses descriptive analysis using criteria average of absorption students after applying cooperative learning model type TGT using media physics circuit in the main optical subject. The finding of the analysis of the data indicated that average of absorption students in the experimental class is 82,75% with good category and in the control class is 75,13% with good category. Therefore, it can be concluded that the application of cooperative learning model type TGT using media physics circuit can improve learning outcomes students in the optical subject at VIII4 class of SMPN 34 Pekanbaru.Kata Kunci: Cooperative Learning Model Type TGT, Media Physics Circuit,Learning Outcomes Students.